Direct amination of boron‐doped diamond by plasma polymerized allylamine film. Issue 10 (14th July 2014) - Bogdanowicz, R.; Sawczak, M.; Niedzialkowski, P.; Zieba, P.; Finke, B.; Ryl, J.; Ossowski, T.
Abstract : A novel microwave pulsed‐plasma based method for the modification of the hydrogen‐terminated polycrystalline boron‐doped diamond (BDD) with a thin film of polymerized allylamine (PPAAm) is reported. A modified BDD surface is resistant to hydrolysis and delamination and is characterized by a high density of positively charged amino groups. Pulsed microwave plasma was applied to improve the degree of cross‐linking and bonding of the plasma polymeric films to BDD. The primary amino groups of the amine‐modified Si/BDD surface were coupled with antraquinone derivatives as model electroactive compounds. Synthesized thin BDD‐PPAAm films were investigated with X‐ray photoelectron spectroscopy (XPS), laser induced fluorescence (LIF) and Fourier transform infrared spectroscopy (FT‐IR). The FT‐IR studies confirm that the molecular structure of the deposited layer reproduces the monomer structure with a partial transformation of amino groups into amide and nitrile. XPS results show that PPAAm film on an Si/BDD electrode is electrochemically stable within the range of polarization potentials between −1.1 and +1.1 V. The fluorescence properties of the PPAAm modified BDD surface makes its promising for application in sensors with optical readout. At the same time, the PPAAm film's durability investigated over a wide potential range makes it ideal for electrochemical sensors.